Interspecies Differences in Reaction to a Biodegradable Subcutaneous Tissue Filler: Severe Inflammatory Granulomatous Reaction in the Sinclair Minipig. (February 2015) - Ramot, Yuval; Touitou, Dan; Levin, Galit; Ickowicz, Diana E.; Zada, Moran Haim; Abbas, Randa; Yankelson, Lior; Domb, Abraham J.; Nyska, Abraham
Soft tissue filler products have become very popular in recent years, with ever-increasing medical and aesthetic indications. While generally considered safe, the number of reported complications with tissue fillers is growing. Nevertheless, there is no specific animal model that is considered as the gold standard for assessing safety or efficacy of tissue fillers, and there are very little data on interspecies differences in reaction to these products. Here, we report on interspecies differences in reaction to a subcutaneous injectable co-polyester, composed of castor oil and citric acid. Comparison of the histopathological local tissue changes following 1-month postimplantation, indicated that in rats the reaction consisted of cavities, surrounded by relatively thin fibrotic enveloping capsule. In contrast, an unexpected severe inflammatory granulomatous reaction was noticed in Sinclair minipigs. To our knowledge, this is the first report on significant interspecies differences in sensitivity to tissue fillers. It emphasizes the importance of using the appropriate animal model for performing preclinical biocompatibility assays for biodegradable polymers, tissue fillers, and implanted medical devices in general. It also makes the Sinclair minipig subject for scrutiny as an animal model in future biocompatibility studies.